The effectiveness of the training protocol based on acceptance and commitment on psychological distress and parenting stress of mothers with deaf children - Fatemeh Nikkhoo; Somaiyeh Fathipoor (مطالعات روانشناسی تربیتی)
The mental pressure caused by having a deaf child has tremendous effects on mothers. This pressure leads to psychological distress and parenting stress for mothers. Therefore, the aim of this study was to investigate the effectiveness of the training protocol based on acceptance and commitment on the psychological distress and parenting stress of mothers with deaf children. The current research was a semi-experimental type with pre-test-post-test and control group. The statistical population was all mothers with deaf children in Tehran. Among these mothers, 30 mothers were selected by available sampling method and then randomly assigned to two experimental and control groups equally. The instrument of this study was the scale of psychological distress and stress of the overbearing child. The sessions of the experimental group consisted of 8 90-minute sessions of acceptance and commitment-based therapy (Bond et al., 2011), which were implemented as a group. Data were analyzed using multivariate analysis of covariance. The results showed that the training protocol based on acceptance and commitment has led to the reduction of psychological distress and parenting stress of mothers (p<0.05). Based on the obtained results, the training protocol based on acceptance and commitment is effective in reducing psychological distress and reducing parenting stress. The results of this study can be effective in helping to reduce the psychological problems of families with deaf children and thus reducing the mental health costs of these families.